Genomic insights into multidrug-resistance and virulence in a vancomycin-resistant Staphylococcus aureus strain VR480 - Nguyen, Quang Huy; Nguyen , Thai Son; Nguyen Thai, Uyen Thu; Nguyen , Thuy Duong; Tran Thi , Thanh Tam (Academia Journal of Biology, 2024)
Vancomycin-resistant Staphylococcus aureus (VRSA), a “high priority antibiotic-resistant pathogen”, is emerging and threatening global health. Nevertheless, molecular mechanisms associated with virulence and multidrug resistance in VRSA are not fully investigated particularly in low- and middle-income countries. Here, for the first time, the complete genome of a VRSA strain VR480 isolated from a Vietnamese patient was generated by the combination of long- and short-read sequencing technologies. The VRSA strain VR480 was a multidrug-resistant phenotype with resistance to at least one antibiotic belonging to beta lactams, quinolones, lincomycin, oxazolidinones, tetracyclines, glycylcyclines, macrolide/lincosamide/streptogramin, nitrofurans, rifamycins, sulfonamides and glycopeptides. This strain was classified as vancomycin resistance (MIC ≥ 32 μg/mL). VRSA strain VR480 belonged to sequence type ST2779 and carried the SCCmec type II(2A). The VRSA strain VR480 genome contains five resistance mutations in genes. gyrA S84L, parC S80F, parE D432N, fusA L461K and glpT W355Stop, and eleven antibiotic resistant genes including mecA, mecR, mecI, tetM, tet38, mepA, lmrS, ant(9), ermA, fosB and catA. This strain possesses various virulence factors associated with adherence, biofilm formation, colonization, invasion, anti-phagocytosis and toxicity that promote the infection and pathogenesis. Protein interaction network analysis revealed five clusters consisting of known and putative virulence proteins. Furthermore, epimerase, EssC, IcaA, SplA and Ssl1 were the key proteins within each cluster. This study raises a warning about the circulation and dissemination of VRSA in Vietnam. The key proteins would be potential targets for the development of anti-virulent agents to combat the VRSA infection.